Optimalisasi Produk Ketahanan Pangan melalui penerapan bisnis kreatif pada UMKM di Desa Samili - Sri Ernawati; Firmansyah Kusumayadi; Muthia Hanifah; Rizkiatun Ramdinah; Junita Adiratwan; Hairunnas (LP3M Universitas Putra Bangsa, 2025)
This community service initiative originated from the KKN–Berdampak (Community Service Program with Impact) conducted by students of the Bima College of Economics (STIE Bima). The program was motivated by the limited product innovation, insufficient understanding of branding strategies, and the lack of digital technology utilization among food-based MSMEs, which consequently weakens their competitiveness and contribution to regional food security. The implementation methods included field observations to identify local food potential, socialization on the importance of creative business, product innovation training, digital marketing workshops, mentoring on design and branding, as well as evaluation and monitoring of program outcomes. The results showed improved participants’ abilities in developing creative food products, enhancing packaging and brand identity, and utilizing digital media for marketing. Through this creative and innovative approach, the program successfully encouraged MSMEs to become more independent, adaptive, and competitive in supporting sustainable food security.